POLA DISTRIBUSI RANTAI PASOK JARINGAN MADU HUTAN SUMBAWA (JMHS) DI KABUPATEN SUMBAWA, NUSA TENGGARA BARAT - Qashiratuttarafi Qashiratuttarafi; Andriyono Kilat Adhi; Wahyu Budi Priatna (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2019)
This study was aimed to analyze the supply chain distribution patterns of forest honey in the West Sumbawa through Sumbawa Forest Honey Network or Jaringan Madu Hutan Sumbawa (JMHS) using descriptive qualitative data. This study uses a supply chain distribution pattern approach based on the product, financial and information flow. In the product flow, honey is harvested by honey hunters in the forest and assembled to a group leader. Then, honey is handed over to JMHS and marketed at Rumah Madu” (Honey House). The forest honey harvest season in Sumbawa is between August-December. Honey hunters can harvest 15-20 liters of honey per hunter in one hunting day. In financial flow, we observed that the pricing of honey is decided by JMHS according to the market price and the harvest season. Honey price from the hunter is ranging from 60,000 - 75,000 IDR per 660 ml bottle. The purchasing price of honey by JMHS is 65,000-85.000 IDR per 660 ml bottle and after the packaging by JMHS, honey is marketed to the last consumers with a selling price of 110,000 IDR per 500 ml. The information flows in both directions. The group of honey hunters inform to JMHS about the locations of honey as well as the amount of harvested. In the JMHS side, they distribute information of the classification and quality of honey, provide the good harvest training and information on honey price to hunters.